Integrating biological and chemical CO2 sequestration using green microalgae for bioproducts generation - Abraham, Juliana; Prigiobbe, Valentina; Abimbola, Tobi; Christodoulatos, Christos (Frontiers in Climate, 2023)
Microalgae cultivation is considered an attractive negative emission technology (NET) due to its ability to remove carbon dioxide (CO2) from the atmosphere as well as from flue gases. Moreover, some microalgae can uptake dissolved carbon in the form of bicarbonate (HCO3-) and grow well by removing nutrients from various wastewater effluents without competing with freshwater resources. Conventional carbon mineralization is another NET where carbon is fixed into carbonate minerals such as calcite (CaCO3), magnesite (MgCO3), nesquehonite (MgCO3-3H2O), and nahcolite (NaHCO3), which can be reused in various applications such as construction and cosmetics, and in this case, to supply carbon to microalgae. Previous initial laboratory studies demonstrated the possibility of using metastable carbonates as a source of carbon for biomass growth of the freshwater microalga Scenedesmus obliquus. In this study, we present results from an experimental and modeling work where 100 L open raceway reactors were used to grow an algae polyculture using industrial nitrogen-rich wastewater. In addition, carbonates such as MgCO3-3H2O and sodium carbonate (Na2CO3) were added to the ponds to primarily buffer the pH and maintain it within the acceptable algae physiological values and to provide extra carbon to the cultures. Cultures using BG-11 growth medium and without addition of carbonates were run as controls. Continuous online monitoring of pH, temperature, and dissolved oxygen was performed while nutrients content and dry weight of algae culture were measured offline daily. A mathematical geochemistry-based model was implemented to describe the overall process of algae growth, carbonate dissolution, and solution composition. Biomass harvested from the raceway reactors was concentrated and oil and fatty acid methyl esters (FAME) content were determined. Results showed that biomass and oil content obtained was comparable to controls, indicating a successful metabolic-based pH control by the addition of carbonates in the ammonium-based media. Furthermore, FAME analysis revealed different profiles depending on the source of carbon used. Overall, this study suggests that integrating both types of NET can contribute to the reduction of carbon emissions while producing biomass that can be further processed to generate a variety of bioproducts.